Legal Philosophy Review of The Authority to Add Norms in the Constitutional Court Decision No. 90/PUU-XXI/2023 - Oktapani, Silm; Libra, Robert (Faculty of Law, Universitas Pekalongan, 2024)
The Constitutional Court (MK) has a central role in maintaining the constitutionality of laws in Indonesia. One of its important functions is to review laws against the 1945 Constitution. However, the Constitutional Court's review should still respect the authority of the legislative power as the legislator. On the contrary, the addition of provisions occurred in Constitutional Court Decision No. 90/PUU-XXI/2023. The problems raised in this research are the position of Consitutional Court as the guardian of the constitution and the legal philosophy review of the authority to add norms in the a quo decision. The method used is normative juridical with a statutory, conceptual, and philosophy approach. The Constitutional Court did not reflect as the guardian of a quo decision. Then, philosophical analysis of the a quo decision found the following points: 1) in terms of positivism, the Constitutional Court exceeded its authority; 2) the addition of provisions in a quo decision has significant impact on national legislation; and 3) the limitation of the Constitutional Court's authority in adding provisions in its decision.